Challenges of schistosomiasis control in Africa: The path ahead - Ejovwokeoghene Joseph Omohwovo; Kebabonye P. Gabaake; Don Eliseo Lucero‐Prisno III (Public Health Challenges, 2024)
Abstract Schistosomiasis is a neglected tropical disease that is endemic in sub‐Saharan Africa, with over 90% of global cases occurring in the region. Poverty, inadequate healthcare infrastructure, and limited access to water and sanitation contribute to the high prevalence of the disease. Despite efforts to control and prevent the transmission of schistosomiasis, a reduction in the transmission rates has not been realized owing to several challenges. This article highlights the challenges of schistosomiasis control in Africa and recommends strategies for successful interventions. These strategies include prioritizing government backing, investing in academic partnerships, strengthening integrated health programs, targeting communities through the primary healthcare system, and adopting home‐grown solutions. Additionally, it is essential to address the knowledge gap hindering effective control of the disease and the risk of reinfection after treatment. By implementing these strategies, it is possible to achieve the World Health Organization's 2021–2030 goal of eliminating schistosomiasis as a public health problem and reducing its prevalence of heavy infection to less than 1%.